Balanced care in managing hepatoblastoma in a patient with trisomy 18: A case report - Lori-Anne Lajeunesse; Mona Beaunoyer; Monia Marzouki; Caroline P. Lemoine (Journal of Pediatric Surgery Case Reports)
Introduction: Despite a high mortality rate during the first year of life, an increasing number of patients with Trisomy 18 (T18) survive into childhood. Offering invasive medical and surgical procedures to this population continues to raise ethical questions. We present the case of a child with T18 and hepatoblastoma, highlighting therapeutic and ethical challenges. Case presentation: A 2.5-year-old female with T18 known for a bicuspid aortic valve and developmental delay presented with an abdominal mass. Alpha-fetoprotein level was elevated (46,540 ng/mL) and imaging showed a single exophytic segment 5–6 liver mass and no metastatic disease, compatible with a PRETEXT II hepatoblastoma. Multidisciplinary discussions took place focusing on treatment options, the patient's quality of life, and her global prognosis. Given the patient's overall good condition, few comorbidities, and the family's wishes to proceed with curative measures, a bisegmentectomy 5,6 was performed. The patient was discharged 12 days postoperatively having suffered no surgical complication. Pathology revealed a mixed epithelial and mesenchymal hepatoblastoma. She received two cycles of adjuvant chemotherapy (cisplatin) without suffering from any complication. Now 5.5 years post-treatment, she remains disease-free. The family is grateful their daughter's chromosomal anomaly did not negatively influence medical and surgical teams in offering her optimal treatment options. Conclusion: Unless suffering from severe underlying medical comorbidities, patients with T18 and hepatoblastoma can receive gold standard care. Multidisciplinary collaboration involving surgeons, medical providers, as well as families are essential to determine optimal individualized treatment strategies.